SEMANTIC-COGNITIVE PECULIARITIES OF THE CONCEPT THUNDER IN THE ENGLISH AND UKRAINIAN LANGUAGE - Pyliachyk, N. Ye.; Bilyk О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the analysis of semantic and cognitive peculiarities of the concept THUNDER in the English and Ukrainian languages. Isomorphic and allomorphic meanings of the lexical units comprising the structure of the investigated concept have been revealed. The phraseological units with such components as storm, thunder and lightning have been analysed. A great interest has been taken in the lexical and semantic lacunar process in the contrasted languages. It is focused on the usage of direct and derived meanings of the nouns that may reveal the ambiguous perception of natural phenomena and categorization of the surrounding reality by the native speakers of English and Ukrainian.